Electrolysis Assisted Biomass Gasification for Liquid Fuels Production - Mesfun, Sennai; Engvall, Klas; Toffolo, Andrea (Frontiers in Energy Research, 2022)
Gasification is a promising pathway for converting biomass residues into renewable transportation fuels and chemicals needed to comply with the ambitious Swedish environmental targets. The paper investigates the integration of a molten carbonate electrolysis cell (MCEC) in biofuel production pathway from sawmill byproducts, to improve the performance of gas cleaning and conditioning steps prior to the final conversion of syngas into liquid biofuels. The energy, material, and economic performance of process configurations with different gasification technologies are simulated and compared. The results provide relevant information to develop the engineering of gas-to-liquid transportation fuels utilizing renewable electricity. The MCEC replaces the water-gas shift step of a conventional syngas conditioning process and enables increased product throughput by as much as 15%–31%. Depending on the process configuration and steam-methane reforming technology, biofuels can be produced to the cost range 140–155 €/MWh in the short-term.